2019
DOI: 10.1016/j.sdentj.2019.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of three-rooted mandibular permanent first and second molars in the Saudi population

Abstract: IntroductionThis study aims to explore the frequency and factors affecting the prevalence of an extra root in the lower first and second permanent molars in the Saudi population.MethodsImages of 379 Saudi patients who underwent CBCT for routine dental treatment were assessed. The CBCT images were evaluated on a 34-inch LED screen in a dark room and assessed by two examiners to count the prevalence of an additional root in the lower molars. Laterality and the gender factors were used to analyze that prevalence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
4
9
1
Order By: Relevance
“…In addition, 3-rooted molars were observed in higher incidence in the first molars (5.5%) than in the second molars (1.7%), consistent with a recent report on the Saudi population (3.05% and 1.48% for first and second molars, resp.) [ 2 ]. Other studies in different populations have shown a similar lower prevalence of extra rooted molars [ 34 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, 3-rooted molars were observed in higher incidence in the first molars (5.5%) than in the second molars (1.7%), consistent with a recent report on the Saudi population (3.05% and 1.48% for first and second molars, resp.) [ 2 ]. Other studies in different populations have shown a similar lower prevalence of extra rooted molars [ 34 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…He reported that the majority of the mandibular second molars had two roots and three canals, with 57% of the mesial roots having type IV configuration and 97% of the distal canal having a type I configuration [ 42 ]. In a study published by Kantilieraki et al, 64.1% had a type II configuration in the mesial canal and the distal canal had a type I configuration in 97.7% in mandibular second molars in the Greek population [ 2 ]. In the study published by Torres et al, in Belgian and Chilean populations, 37.2% of the mesial roots of mandibular second molars had a type III configuration, 28.7% had a type V configuration in the Belgian population, 48.4% had type III canals, and 20.6% had type V configuration in the Chilean population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations